Plate Fixation for Unstable Displaced Distal Radius Fractures in Children - van Egmond, Jeroen C.; Selles, Caroline A.; Cleffken, Berry I.; Roukema, Gert R.; van der Vlies, Kees H.; Schep, Niels W.L. (Journal of Wrist Surgery, 2019)
Background Distal radius fractures in children are normally treated by plaster immobilization. For displaced unstable distal radius fractures, closed reduction and Kirschner wire (k-wire) fixation can be performed. Disadvantages of k-wire fixation are the need for postoperative plaster treatment for several weeks, which may induce stiffness, and the risks of complications such as tendon irritation and pin-track infections. More invasive volar plate fixation is less popular, although this allows for direct mobilization and enhances anatomical reduction.Purpose To present the functional outcomes of pediatric patients treated with volar plate fixation for unstable displaced distal radius fractures.Patients and Methods A retrospective cohort study of all consecutive pediatric patients between September 2010 and July 2017 was performed. A total of 26 patients with a median age of 12.5 years were included. The primary objective was functional outcome determined by the Patient-Rated Wrist Evaluation (PRWE) questionnaire. Secondary objectives were range of motion, grip strength, radiological parameters, complications, and incidence of plate removal.Results Median PRWE score was 3 after a median follow-up of 29 months. Range of motion and grip strength did not differ significantly between the injured and uninjured wrists. No wound infections were found. Plate removal was performed in 15 patients (58%).Conclusion Volar plate fixation for unstable displaced distal radius fractures in children provides good functional and radiological outcomes with minor complications.Level of evidence This is a Level IV cohort study.
Keywords: distal radius; fracture; plate fixation; pediatric; children